2018
DOI: 10.3389/fphys.2018.01223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Autophagy-Related Gene 7 and Autophagic Cell Death in the Planarian Dugesia japonica

Abstract: Planarians undergo continuous body size remodeling under starvation or during regeneration. This process likely involves autophagy and autophagic cell death, but this hypothesis is supported by few studies. To test this hypothesis, we cloned and characterized autophagy-related gene 7 (Atg7) from the planarian Dugesia japonica (DjAtg7). The full-length cDNA of DjAtg7 measures 2272 bp and includes a 2082-bp open reading frame encoding 693 amino acids with a molecular weight of 79.06 kDa. The deduced amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Autophagy is an evolutionary conserved mechanism that occurs continuously to maintain the homeostasis of all tissues (González-Estévez and Saló, 2010). During planarian regeneration, they undergo continuous body remodeling and no food can be taken until the formation of a new functional pharynx (Ma et al, 2018a). Therefore, cell death caused by autophagy is necessary as a natural consequence of restricted food availability to maintain tissue homeostasis (González-Estévez, 2008, 2009; González-Estévez and Saló, 2010; Reddien, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Autophagy is an evolutionary conserved mechanism that occurs continuously to maintain the homeostasis of all tissues (González-Estévez and Saló, 2010). During planarian regeneration, they undergo continuous body remodeling and no food can be taken until the formation of a new functional pharynx (Ma et al, 2018a). Therefore, cell death caused by autophagy is necessary as a natural consequence of restricted food availability to maintain tissue homeostasis (González-Estévez, 2008, 2009; González-Estévez and Saló, 2010; Reddien, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that autophagy occurs in newly regenerated planarians on days 7 and 10 after amputation through TEM investigation (Ma et al, 2018a). Interestingly, the remodeling process can occur by autophagy activation in Polycelis tenuis and only two peaks for acid phosphatase activity (autophagy marker) were observed (Bowen et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention has been shifted from higher eukaryotes (e.g. yeast) to invertebrates in identifying the cellular basis of autophagy and the homologs of ATGs [ 52 54 ]. During evolution, ATGs have been duplicated and lost, thus resulting in the extinction and expansion of some subfamilies of autophagy-related genes.…”
Section: Atg Family and Mtorc1-related Remodeling Within Invertebratementioning
confidence: 99%